2000
DOI: 10.1021/jp992591p
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Approach to Investigate Gated Electron Transfer Using a Physiological Model System:  Cytochrome c Immobilized on Carboxylic Acid-Terminated Alkanethiol Self-Assembled Monolayers on Gold Electrodes

Abstract: The electron transfer (ET) scheme of cytochrome c (cyt. c) coupled to carboxylic acid-terminated alkanethiol self-assembled monolayers (SAMs) on well-defined gold (111) electrodes is a simplified model system to investigate both long range and intermolecular ET processes. The advantages of an electrochemical approach to investigate the ET mechanism are that one can both regulate the ET path length by using alkanethiol SAMs of varying chain lengths and deconvolute the intermolecular ET event at the interface f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
318
4
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(372 citation statements)
references
References 73 publications
(140 reference statements)
48
318
4
2
Order By: Relevance
“…Configuration gating here means that the rate-limiting step of ET through short alkyl chains is a configurational rearrangement process of adsorbed azurin. Similar phenomena were found also for cytochrome c adsorbed electrostatically on carboxylic acid-terminated alkanethiol selfassembled monolayers (41). Configuration gating could thus play a significant role in determining the interfacial ET kinetics of such molecular wiring-based protein ET systems.…”
Section: Resultssupporting
confidence: 70%
“…Configuration gating here means that the rate-limiting step of ET through short alkyl chains is a configurational rearrangement process of adsorbed azurin. Similar phenomena were found also for cytochrome c adsorbed electrostatically on carboxylic acid-terminated alkanethiol selfassembled monolayers (41). Configuration gating could thus play a significant role in determining the interfacial ET kinetics of such molecular wiring-based protein ET systems.…”
Section: Resultssupporting
confidence: 70%
“…Previous studies that exploited SAM-coated electrodes revealed two kinds of phenomenological behavior (17)(18)(19)(20)(21)(22)(24)(25)(26)(27)(28)(29)(30)(31). For the case of thicker SAMs (long-range ET), these studies showed an exponential decay of k et with the SAM thickness (that is a part of the ET distance, R e ); in accordance with the nonadiabatic ET (tunneling) theory (1, 3, 17-22, 24-32, 46-50):…”
supporting
confidence: 75%
“…This behavior has been attributed to a number of mechanisms: (i) dynamic modes of the solvent or protein interior that damp motion along the ET reaction coordinate (so-called ''quantum friction'') (42); (ii) electrode-derived electric field effects that influence proton rearrangements (43); and (iii) larger amplitude gating processes that produce transitions between active vs. inactive states (44)(45)(46). In the electrochemical systems, ET rates plateau in the same range that we observe for the ZnCcP:Cc complexes (200-5,000 s Ϫ1 ) (14,42,44,45). The CcP:Cc crystal systems show that leveling behavior is an intrinsic property of interfacial protein ET and not unique to electrodes.…”
Section: Structures and Redox Properties Of Znccp In Complex With Yccmentioning
confidence: 99%